Acute Oral Toxicity Analysis of Nano-Hydroxyapatite-Gelatin Suspension in Albino Wistar Rats - Malla, Komal Prasad; Malla, Bindu; Pandit, Rajesh; Pokharel, Shanta; Yadav, Ram Jeewan; Adhikari, Rameshwar (Journal of Nepal Chemical Society, 2024)
Hydroxyapatite (HAp), a calcium phosphate-based bio-ceramic, was prepared from waste ostrich bone using the thermal decomposition method, and the nano-HAp was segregated by the water-in-oil microemulsion technique. A single acute dose of oral toxicity of nano-HAp in gelatin suspension was tested in eleven female Albino Wistar rats following the OECD 420 guidelines. The rats were divided into three groups: three for control, three for group I, and five for group II. The first group was given 300 mg of nano-HAp in gelatin suspension per kg of body weight, while group II was given 2000 mg per kg of body weight. Results show that no signs or symptoms of toxic effects were seen in the group during the 14-day study period. Furthermore, no significant change in their average body weight or other physical behaviors such as autonomic, respiratory, or somatomotor effects were observed in the rats. The macroscopic examination of internal organs and bodyweight observation have shown no symptoms of toxicity in either group. It could be concluded that the nano-HAp suspension in gelatin does not show any acute toxic effect. The lethal 50% dose (LD50) of the nano-HAp-Gel suspension has been estimated to be more than 2000 mg/kg of the body weight, suggesting that nano-HAp extracted from ostrich bone is safe to use for calcium supplements and other biomedical applications.